KEBIJAKAN USAHA KESEHATAN SEKOLAH/MADRASAH: Implementasi pada Lembaga Pendidikan Berbasis Pesantren di Kabupaten Banyuwangi - M. Mahmud (LP2M Universitas Ibrahimy, 2018)
This paper aims to explain that the implementation of School Health Unit (UKS/M) policy in pesantren based education institution in Banyuwangi Regency is not ideal with what is stated in the decision of 4 Ministers (SKB 4 Ministers) namely Minister of Health, Minister of Religious Affairs, Minister of Education and Culture, and the Minister of Home Affairs on the development and development of School Health Unit (UKS/M). This research is a descriptive research taken from qualitative data in the form of field observation, interview, and documentation as the material of analysis, so that writer can find important findings. 1) implementation of the School Health Unit (UKS/M) trias in schools under the auspices of pesantren cottages most of them have not been properly implemented; 2) coordination of the 4 elements of the ministry has not been well established; 3) the absence of adequate human resources such as not understanding their duties and obligations, the financial resources of the state budget has not been realized, and equipment resources (facilities required) is not complete even there are schools that do not have at all; 4) the willingness for the implementation of UKS/M from the four elements of the ministry is still in the form of planning; 5) the organizational structure of the UKS/M facilitation team from the 4 ministries has not been established; 6) the implementation of coaching and development of UKS/M is only done by the health department only.